Powierzanie przez gminę zadań podmiotom zewnętrznym i odpowiedzialność za ich nienależyte wykonanie na przykładzie zimowego utrzymania czystości i porządku - Strzelbicki, Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
This paper aims to present aselection of legal issues related to the commune’s tasks of keeping roads, pavements and other public areas clear and safe during winter time and the execution of such tasks by means of delegating them to external entities. As arule, the legislator decided that it is the commune which is responsible for ensuring that places accessible to the public are well-maintained in the winter. This responsibility, which includes as well removing snow and ice that has been cleared from pavements by the owners of adjacent properties, belongs to the category of public-interest tasks and therefore may be performed by the commune using its own units including local budgetary entity or may be entrusted under an agreement on delegation of the task to an external entity. It is worth noting that even with the task of winter maintenance being delegated to the external entity, it is the commune that remains responsible and liable, both under public law and under the provisions of the Civil Code. If snow clearing is delegated to external professionals, the commune is indemnified against damage caused by the actions of such entities, but the commune still remains liable for damages when athird party suffers any loss in property or personal injury as aresult of an external entity’s non-performance or improper performance of tasks delegated thereto. Therefore, establishing cooperation with aprivate entity by delegating the task in question to such entity cannot be used by the commune as ameasure to circumvent the problem of winter maintenance, which is one of the obligations assigned to the commune under the applicable law.
Keywords: gmina; powierzanie zadań; podmioty zewnętrzne; odpowiedzialność za nienależyte wykonanie; zimowe utrzymanie czystości i porządku